Community forestry and peoples livelihoods (Journal of Forest and Livelihood, 2024)
Journal of Forestry and Livelihood ForestAction16 LIVELIHOODS, ECONOMIC OPPORTUNITY AND EQUITY The author highlights the successes of community forestry in improving local livelihoods. Using a livelihood framework, he assesses the nature and extent ofcontributions of community forestry in improving the different livelihoods capitals – including social and human, natural, and physical. He also identifies broader positive changes in social, organizational and policy aspects. Finally, some challenges ahead are also identified.